Factors influencing the use of M-commerce: an extended technology acceptance model perspective - Barry, Moussa; Jan, Muhammad Tahir (2018)
The application of m-commerce activities among smartphone users in Malaysia has become one of the major challenges for companies involved in m-commerce. The present study aims at identifying the factors influencing m-commerce use in Malaysia. An extended Technology Acceptance Model (TAM) is employed. A total of 350 questionnaires were distributed among smartphone users in the Klang Valley area of Malaysia. Two-stage Structural Equation Modelling (SEM) was employed to test the model of the study. The findings of the study reveal that behavioral intention has a significant positive influence on m-commerce use. The findings further reveal that perceived usefulness, perceived enjoyment, and privacy and security have significant positive influence on behavioral intention. These findings will benefit stakeholders involved in m-commerce activities such as providers, retailers, brands, and consumers. In addition, academicians and students can also benefit from this study in the context of m-commerce use in Malaysia.